USE OF VARIOUS EFFECTIVE METHODS IN TEACHING BIOLOGY - Z.R.Abdusalomova; M.J.Tolibova; N.R.Turniyozova, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article we discuss variouseffective methods of teaching biology. Information about various methods, excursions and the use of information technology and teaching of biological sciences, as well as ethical methods, can be of interest to students of practical interest.